How do you find (f*g)(x) and (g*f)(x) and determine if the given functions are inverses of each other f(x) = x^2 − 3f(x)=x23 and g(x) = sqrtx+3g(x)=x+3?

1 Answer
Jan 24, 2017

To find f(g(x)) and g(f(x))f(g(x))andg(f(x)), substitute, g(x) for x in f(x), and f(x) for x in g(x), respectively. If they are inverses, both substitutions will equal x.

Explanation:

f(g(x)) = (sqrt(x) + 3)^2 -3f(g(x))=(x+3)23

f(g(x)) = x + 6sqrt(x) + 9 -3f(g(x))=x+6x+93

f(g(x)) = x + 6sqrt(x) + 6f(g(x))=x+6x+6

g(f(x)) = sqrt(x^2 - 3) + 3g(f(x))=x23+3

They are not inverses, because both cases must reduce to x.